COMMUNICATION STRATEGIES FOR CHILD PROTECTION IN ADDRESSING ONLINE GROOMING IN INDONESIA - Suci Ramadhani Putri (Akademi Bisnis Lombok, 2025)
Online grooming has emerged as a critical threat to child safety in Indonesia's rapidly digitalizing society. This study examines communication strategies for child protection against online grooming through a comprehensive library research methodology, analyzing statistical data, legal frameworks, and existing literature. The research reveals that despite legal protections under Law No. 1 of 2023 on the Criminal Code, Law No. 19 of 2016 on Electronic Information and Transactions, and Law No. 35 of 2014 on Child Protection, implementation gaps persist. Key findings indicate that effective protection requires multi-stakeholder collaboration involving families, educational institutions, government agencies, and civil society organizations. The study identifies six critical dimensions: understanding online grooming patterns, digital literacy enhancement, family communication strengthening, educational institution roles, legal framework effectiveness, and integrated protection strategies. Recommendations emphasize the need for comprehensive digital safety education, strengthened reporting mechanisms, and culturally-sensitive prevention programs that align with Indonesian Islamic values and local wisdom.